The economical use of antibiotics to prevent infection after herniated disc surgery - صالح علي محمد; جمال سليمان (Latakia University Journal -Medical Sciences Series, 2023)
Introduction: To highlight the unjustified overuse of perioperative antibiotics in clean non-instrumented lumbar spinal surgeries. To convince orthopedic surgeons in a methodological way of local field comparison between common practice on the use of perioperative antibiotics prophylaxis (PAP) in clean non-instrumented lumbar spinal surgeries and the ideal practice according to "The guidelines published by North American Spine Society (NASS)". Methods: A complete audit cycle had been done. One hundred and eight patients underwent clean non-instrumented lumbar spinal surgeries in a tertiary spine center, during the period from the 1st of April to the 31st of June 2017 (primary audit period) and during the period from the 8th of May to the 21st of November 2018 (re-audit period). Group I: audit group (n = 54) was given the usual regimen (IV first-generation cephalosporin for 1-6 days, followed by oral antibiotics, till the removal of stitches) and Group II: re-audit group (n = 54) received only the IV antibiotics for one day). The study protocol was approved by our institution’s Ethical Committee (17100582). Results: This study showed a wide gap between international standards and local prescribing practices and calls for multiple interventions to improve our practice. Out of the 108 patients, only one case (1.85%) developed surgical site infection (SSI) in the audit group (Group I). The difference in infection rates between the two groups was statistically insignificant. Conclusion: A single-day postoperative dose of antibiotics effectively prevents postoperative wound infection following non-instrumented lumbar spinal surgery and is not associated with a higher infection rate.